ENHANCING EARLY READING COMPETENCE THROUGH WHOLE WORD METHOD-BASED SCRAPBOOK MEDIA IN ELEMENTARY SCHOOLS - Julyanur Suci Wardayati Di Ningrum; Destrinelli; Muhammad Sofwan (El Midad, 2025)
This study was motivated by the low early reading skills of elementary school students, which were caused by mechanistic learning practices and the lack of engaging instructional media suitable for children’s developmental characteristics. This problem highlights the need for innovative learning approaches that emphasize visual experiences, motor activities, and contextual meaning comprehension. The purpose of this study was to develop a scrapbook media based on the Whole Word Method as an effort to enhance elementary students’ early reading competence. This study employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 25 first-grade students and one classroom teacher at SD Negeri 162/IV, Jambi City. The results indicate that the developed scrapbook media met the criteria of very high validity with a score of 91.4%, high practicality with a score of 93.7%, and effectiveness, with the average score increasing from 63.5 to 87.2 (N-Gain = 0.65, medium–high category). The scrapbook media proved capable of improving students’ early reading skills through contextual, visual, and enjoyable learning activities. This study recommends that elementary school teachers utilize visually creative media, such as scrapbooks, as an alternative for early-phase literacy instruction.